THE RELATIONSHIP BETWEEN WORKPLACE HAPPINESS AND EMPLOYEES PERFORMANCE - Grace Kayvener, Wesley (Universiti Malaysia Sarawak (UNIMAS), 2021)
The purpose of this study is to identify the relationship between the workplace happiness and employee performance based on the three factors of workplace happiness that influence performance. The respondents used in this study are 50 employees from Divisional Agriculture Office in Miri, Sarawak. Quantitative method was used and 5 points Likert-scale questionnaires were distributed to the respondents. The data were analysed by using descriptive and inferential statistics. Pearson’s Correlation Analysis was used to measure the relationship between the variables to determine the most dominant factors of workplace happiness that affecting the employee performance. From the research findings, there are significant relationships between job inspiration, organization’s shared value, and workplace social relationships with employee performance. Based on the findings, job inspiration is the most dominant factors that affecting the employee performance. In the conclusion section, implication of study was presented, followed by recommendations for organization and future researchers. The organizations can utilise the findings to create a workplace that promote happiness at work for improving employee performance.